Sand as thermoluminescent dosimeter to therapeutic doses (2010)
This work describes the thermoluminescent characteristics of sand from Coveñas beaches for use as a dosimeter in therapeutic doses. Selected samples, heat treated at 400 ° C for one hour, were irradiated at different doses using a 60Co Theratron 780C unit in air at room temperature. The reading was done on a Harshaw TLD 4500. The main dosimetric properties of the material (brightness curve, response reproducibility, reuse, linearity and thermal decay) have been studied in detail. The brightness curve of the sand samples has a TL peak around 145 ° C. The results show that the material has a linear response with the dose from 50 cGy to 1000 cGy. The sand samples studied can be used as thermoluminescent dosimeters for applications in different areas. The importance of this work is that sand is a natural substance available in large quantities, has low cost and can be used in clinical physics to evaluate the dose received by the patient during medical treatment.